THE OFFTATLED PROJECT: OFFensive and TAboo Exchanges SubtiTLED BY ONLINE UNIVERSITY STUDENTS - Ávila-Cabrera, José Javier; Rodríguez Arancón , Pilar (Encuentro Journal, 2018)
The OFFTATLED Project: OFFensive and TAboo Exchanges SubtiTLED by Online University Students. Every culture has its own idiosyncrasies when it comes to what is considered to be taboo language. For this reason these terms are some of the most difficult to translate from the source language into the target language in audiovisual translation. This study aims to report on how a group of university students dealt with this issue when given the task of subtitling clips from several films, both from English into Spanish as well as from Spanish into English. The participants pertained to the Degree in English Studies at the UNED (Universidad Nacional de Educación a Distancia) and were taking a course on English-Spanish translation. The researchers later analysed whether the end results displayed a faithful rendering of the original strength of meaning or if, on the contrary, they reflected any softening of intent and effect. The research also sought confirmation as to whether the students were more daring than the source text itself when subtitling into the foreign language.